Espèces végétales exotiques et vulnérabilité environnementale : un débat ancien ? Le cas de la Belgique (fin XVIIIe siècle-années 1950) - Odile De Bruyn (VertigO, 2016)
A decline in vegetal biodiversity is undoubtedly of paramount importance when one has to assess the environmental vulnerability of a specific biotope. Among other well-known menacing factors such as pollution, climate change, land management and war, there is one ingredient that might seem at first sight less discernible, given its vegetal origin: it is the plantation of alien species in parks, gardens and forested settings. For the last forty years, the distressing effects of alien plants on the environment, whether these were invasive species or not, have been the focus of a fiercely debated question among the scientific community. But what of the past when concepts such as biodiversity or environmental vulnerability were as alien to society as the exotic plants burghers and aristocrats were avidly buying from abroad? In this paper we will try to answer this question. Furthermore, we will show how the introduction of these exotic species caused debates in Belgium from the end of the 18th century to the years following World War II. Considering the main actors of these debates, we will ask ourselves about their arguments as well as their professional backgrounds and social milieu. Finally, we will also assess the part that environmental vulnerability did play in their broader ideas about Nature.